TiO2 supported on activated carbon from tire waste for ibuprofen removal (2020)
Activated carbon from tire waste was synthesized, and TiO2 was supported on it at three proportions (FC1 > FC2 > FC3) to evaluate its performance on the ibuprofen removal under ultraviolet radiation. Activated carbon was characterized by N2 adsorption isotherm at 77 K, proximate analysis, and FTIR. The catalysts were characterized by XRD, FTIR, SEM-EDS, and TGA. The activated carbon was mesoporous with a surface area of 140 m2/g. The pH effect was significant; therefore, FC3 at pH3 and UV light reached removal of 93% in the first 2 min, mainly attributed to adsorption.